2011
DOI: 10.1590/s0365-05962011000700006
|View full text |Cite
|
Sign up to set email alerts
|

Angiodema due to oral acitretin and isotretinoin

Abstract: Angioedema may be caused by nonsteroidal antiinflammatory drugs, angiotensin-converting enzyme inhibitors, radiocontrast media, antibiotics, sea food etc. It can involve an allergic (IgE-mediated) or non-allergic hypersensitivity reaction, both with a similar clinical presentation. While angioedema due to isotretionin has been described previously, this is the first description of angiodema due to acitretin. We report two uncommon cases of palpebral and labial angiodema due to retinoids, by acitretin and oral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Angioedema has only been reported in 3 cases due to the use of isotretinoin and in 1 case due to the use of acitretin to date [35] (Table 1). In one of these cases, both urticaria and angioedema were reported due to systemic isotretinoin treatment in an 18-year-old female referred with facial nodulocystic acne of two years duration [5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Angioedema has only been reported in 3 cases due to the use of isotretinoin and in 1 case due to the use of acitretin to date [35] (Table 1). In one of these cases, both urticaria and angioedema were reported due to systemic isotretinoin treatment in an 18-year-old female referred with facial nodulocystic acne of two years duration [5].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, perioral abscess formation in patients taking isotretinoin may also masquerade as angioedema or severe mucositis [8]. However, to date only one case of a 48-year-old man with bilateral periorbital oedema related to acitretin 25 mg/day use has been reported [3]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 1 occurred from acitretin and the other from isotretinoin. 4 In addition, Saray et al 5 have reported a case of angioedema and urticaria due to isotretinoin.…”
Section: Introductionmentioning
confidence: 99%